Evaluation Of The Implementation Of The Decent Housing Assistance Policy In Minahasa Regency North Sulawesi Province - M, Tasik, Femmy C; Mamentu, Michael; Rares, Rares (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2026)
The housing assistance program is a government program aimed at repairing uninhabitable houses. This program aims to improve the welfare of the poor. The assumption is that with the availability of livable housing, the poor can concentrate more on earning a living for their families. Poverty Severity data released by the North Sulawesi Statistics Agency (BPS) in 2024 shows that Minahasa Regency is at the top with a figure of 0.41%, followed by Talaud Islands Regency at 0.28% and Bitung City at 0.25%. In 2018, the Minahasa Regency government issued a policy on housing assistance through Regent Regulation Number 22 of 2018. However, in reality, this policy was only implemented in 2023. In the following year and until 2025, housing assistance was no longer implemented. This policy turned out to be direct assistance from the Indonesian Ministry of Social Affairs in that year. Field observations revealed that this program was highly beneficial for the recipients, effectively targeting them, and operating as expected. This means that families who previously lacked adequate housing were finally able to own homes through this program. The reality on the ground is that many extremely poor families in Minahasa Regency are still in dire need of their own, decent homes. Therefore, the government is strongly encouraged to continue this affordable housing assistance program.